Spatial and temporal patterns in catch rates from multispecies shark fisheries in Western Australia. (1st November 2021) - Braccini, Matias; Denham, Ainslie; O'Neill, Michael F.; Lai, Eva
Abstract: Time series of commercial catch rates are the most commonly available proxy for shark abundance trends. Biased interpretations of spatial and temporal patterns in commercial catch rates have led to misleading stock status assessments. In this study, we outlined the steps required to account for unbalanced fishery data sets and derive standardised catch rates for the main commercial species taken in the shark fisheries of Western Australia (WA) as a case study. Catch rates peaked early in the year for sandbar (March) and dusky (March–April) sharks but towards the end of the year (September–November) for whiskery sharks. For gummy sharks, catch rates fluctuated throughout the year. Catch rates increased with depth for whiskery and sandbar sharks but decreased with depth for dusky sharks. Spatial hotspots occurred in the southwest and east of 123° E for whiskery sharks, east of 124° for gummy sharks, in the southwest for dusky sharks, and in the west coast between 28° and 30° S for sandbar sharks. Following an initial decline, annual catch rates stabilized in recent years across all species. Our study illustrated the challenges associated with multispecies fisheries data for informing management and conservation, identified spatial hotspots and provided standardised catch rates for use in stock assessments. Given the lower economic value of sharks, fishery-independent surveying is unlikely to be achievable for most species. Hence, applying best practices for standardising available shark fishery-dependent data and communicating the corresponding uncertainty is essential for quantitative assessments. Graphical abstract: Image 1